2016
DOI: 10.1155/2016/5365983
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Integrating MEMS-Based Low-Cost IMU and GPS in Vehicular Navigation

Abstract: In providing acceptable navigational solutions, Location-Based Services (LBS) in land navigation rely mostly on integration of Global Positioning System (GPS) and Inertial Navigation System (INS) measurements for accuracy and robustness. The GPS/INS integrated system can provide better land-navigation solutions than the ones any standalone system can provide. Low-cost Inertial Measurement Units (IMUs), based on Microelectromechanical Systems (MEMS) technology, revolutionized the land-navigation system by virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Toth and colleagues applied neural networks and fuzzy logic [ 10 ] to model IMU error sources. Navidi et al [ 11 ] used hybrid Fuzzy Inference Systems (FIS) and the second-order extended Kalman filter to integrate GNSS and IMU sensors. Xing and colleagues showed that chaotic particle swarm optimization significantly reduced gyroscope random drift [ 12 ].…”
Section: Problem Statementmentioning
confidence: 99%
“…Toth and colleagues applied neural networks and fuzzy logic [ 10 ] to model IMU error sources. Navidi et al [ 11 ] used hybrid Fuzzy Inference Systems (FIS) and the second-order extended Kalman filter to integrate GNSS and IMU sensors. Xing and colleagues showed that chaotic particle swarm optimization significantly reduced gyroscope random drift [ 12 ].…”
Section: Problem Statementmentioning
confidence: 99%
“…Recently, micro-electro-mechanical system (MEMS) gyroscopes have been widely studied and employed in aviation, attitude controlling, and guidance, on account of their excellent precision, fast response, and low cost, among other advantages [1][2][3]. Every coin has two sides, however: the performance of a MEMS gyroscope degrades rapidly with changes in temperature, which can limit its application [4].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this task, an autonomous transport machine must be equipped with a set of sensors that allow it to accurately determine its position relative to the surrounding limits. Currently, the most commonly used navigation systems for agricultural machines are the Global Navigation Satellite System (GNSS), Machine Vision Navigation System, Light Detection and Ranging (LIDAR), and Combined Navigation Systems composed of two or more subsystems [2][3][4][5][6][7]. The most affordable sensor for direct measurement of position, GNSS, does not reach this level of accuracy [8].…”
Section: Introductionmentioning
confidence: 99%